Lesson learned of long-term Fund for elderly dependent participants: A case study of Chaiyaphum Province, Thailand - Pattraa, Sakchai; Walugembe, Francis; Chaiwong, Sanhawat (Journal of Posthumanism, 2025)
This study explores the implementation and outcomes of a long-term care (LTC) fund model for dependent elderly populations in Chaiyaphum Province, Thailand. It emphasizes participatory fund management, integrating local government units, health professionals, and community stakeholders. Through qualitative and participatory action research across twelve case studies, the model demonstrated improvements in budget management, community engagement, and service delivery. Findings suggest that localized, community-based fund management enhances the responsiveness and sustainability of elderly care systems in rural contexts. The study contributes to broader discussions on equity, aging, and participatory governance in health care systems, especially relevant to posthumanist critiques of institutional care.